Elastyczność jako składowa paradygmatu zarządzania współczesnymi organizacjami - Osbert-Pociecha, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article undertakes an attempt to check the following issue: if the flexibility is a crucial component of paradigm of contemporary management? It also describes a multidimensional essence of flexibility and its significance as advisable framework for organization in turbulent environment. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 479-487